Generative AI Usage and Information Literacy Skills among University Students in North-West Nigeria: Generative AI Usage and Information Literacy Skills among University Students in North-West Nigeria - Dada, Kayode Sunday John; Quadir, Opeyemi Romoke (Talenta Publisher, 2026)
This study examined the relationship between generative AI usage and information literacy skills among university students in North-West Nigeria. The research investigated awareness levels, evaluation practices, ethical considerations, and barriers affecting the integration of AI-powered tools in academic contexts. Employing a quantitative research design, the study surveyed 385 undergraduate students from federal, state, and private universities using the Generative AI and Information Literacy Impact Questionnaire (GAIL-IQ). Data analysis utilized descriptive statistics including means, standard deviations, and frequencies through SPSS version 26. The ACRL Framework for Information Literacy (2016) provided the theoretical foundation, emphasizing threshold concepts in information understanding. Findings revealed moderate awareness levels (M=3.42, SD=0.89) of AI-powered tools among students, with significant variations across institutional types. Students demonstrated limited capacity in evaluating AI-generated content credibility (M=2.78, SD=0.94), raising concerns about information accuracy assessment. Ethical practices regarding attribution and academic integrity showed moderate adherence (M=3.15, SD=1.02), though infrastructural constraints and inadequate training emerged as primary barriers (M=3.68, SD=0.87). The study concluded that while students increasingly engage with AI-powered tools, critical evaluation competencies and ethical awareness require substantial improvement. The study recommends that Universities in North-West Nigeria should integrate comprehensive information literacy training programs specifically addressing AI-powered content evaluation, ethical usage frameworks, and attribution practices into undergraduate curricula to enhance academic integrity and critical thinking capabilities.